Kalendarz rolniczy Ḡaylāna w tunezyjskiej kulturze ludowej – między mitem a rzeczywistością: próba analizy socjolingwistycznej - Oueslati, Jamila (Scripta Neophilologica Posnaniensia, 2022)
The aim of this article is to shed light on selected sociolinguistic aspects of one of Tunisian most important agricultural heritage, the agricultural calendar. In Tunisia’s cultural heritage, there is a legend about Ḡaylana, its calendar and the way the agricultural year is divided. Tunisians for generations have believed that the shepherd Ḡaylān created the first agricultural calendar known throughout North Africa as ‘ḥsāb Ḡaylān’ ( (حساب غيلان [Ḡaylān’s calendar], ‘il-yawmiyya il-filāḥiyya’ ( اليومية الفلاحية ) [agricaltural calendar] also called ‘il-yawmiyya il-ʽarbī’ ( اليومية العربي ) [Arabic calendar]. The language spoken by Tunisian farmers on a daily basis is full of words and expressions that are hard to find in the language of city dwellers who perceive time according to the solar (Gregorian) calendar. This makes it possible to speak of a Tunisian agricultural dictionary. Everyday language, customs and work of farmers are closely related to the passing of the year. This cycle gives rhythm to the lives of the older generation of Tunisians. The research material that has been collected confirms the richness of the agricultural dictionary, and the analytical and comparative research shows the specificity of agricultural vocabulary, as it is difficult to analyze their language and cultural and social levels separately.